LACK OF MOTIVATION FACTORS CREATING POOR ACADEMIC PERFORMANCE IN THE CONTEXT OF GRADUATE ENGLISH DEPARTMENT STUDENTS - MAULIYA, ISLAHUL; RELIANISA, RESTY ZULEMA; ROKHYATI, UMY (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
At the graduate level, students’ poor performance cuts across almost all the compulsory subjects in which English is inclusive. Poor academic performance of students is one problem impeding the smooth actualization of the educational purpose, which is to prepare an individual for mentally serving both himself and society. Therefore, the primary purpose of this research is to discover the internal factors, such as lack of motivation factors contributing to the poor academic performance of graduate students of the English Department. In this research, researchers selected three participants and utilized an interview as the method to collect the data, and interview guidelines as the instrument. The authors analysed the data qualitatively and explained the findings descriptively. Several things will affect students’ academic performance, especially those related to motivation. It starts from within the students themselves, from the family environment, and even lecturers greatly affect student motivation in improving academic performance. It should not only focus on the mistakes made by students, as there must be a cause behind it all. In a nutshell, the results of this study revealed that one aspect of internal factors causing poor academic performance was the lack of motivation derived from two sizeable directions, family and teacher.